Synthesis, Characterization and Electrical Conductance of Ferrocenylazobenzene - Hegde, Gurumurthy; Tagg, Tei; Siti Athirah, Mohamad Jamali; Hasiah, Salleh (Taylor & Francis, 2014)
Ferrocenylazobenzene was synthesized by condensing an aminoazobenzene dye with ferrocenecarboxylic acid previously treated with oxalyl chloride. The compound displayed an anticipated chemically reversible one-electron oxidation process and gave a formal potential, E° = 0.65 V. In the UV-Vis region, the azo π-π* and n-π* transitions appeared at 355 and 460 nm respectively. On oxidation of the ferrocenyl moiety, the azo π-π* band was blue-shifted to 348 nm with an increase in intensity, while a new broad, lower energy absorption band assigned to the ligand-to-metal charge transfer appeared at 622 nm. The growth of this new band was concurrent with the bleaching of the metal-to-ligand charge transfer band which was largely obscured by the azo n-π* band at 460 nm. The compound in the form of thin film gave an average electrical conductivity of 0.239 ± 0.001 Scm−1 and a non-linear I-V curve with knee voltage at 2.3 V in dark condition.